Structural dynamics in earthquake and blast resistant design - Prasad, B. K. Raghu (Boca Raton, FL : CRC Press, 2020)
Focusing on the fundamentals of structural dynamics required for earthquake blast resistant design, Structural Dynamics in Earthquake and Blast Resistant Design initiates a new approach of blending a little theory with a little practical design in order to bridge thisunfriendly gap, thus making the book more structural engineer-friendly. This is attempted by introducing the equations of motion followed by free and forced vibrations of SDF and MDF systems,D'Alembert's principle, Duhammel's integral, relevant impulse, pulse and sinusoidal inputs, and, mostimportantly, support motion and triangular pulse input required in earthquake and blast resistant designs, respectively. Responses of multistorey buildings subjected to earthquake ground motion by a well-known mode superposition technique are explained. Examples of real-sizestructures as they are being designed and constructed using the popular ETABS and STAAD are shown. Problems encountered in such designs while following the relevant codes of practicelikeIS 1893 2016 due to architectural constraintsare highlighted. A very difficult constraint is in avoiding torsional modes in fundamental and first three modes, the inability to get enough mass participation, and several others. In blast resistant design the constraint is to model the blast effects on basement storeys (below ground level). The problem is inobtaining the attenuation due to the soil. Examples of inelastic hysteretic systemswhere top soft storey plays an important role in expending the input energy, provided it is not below a stiffer storey (as also required by IS 1893 2016), and inelastic torsional response of structures asymmetric in planare illustrated in great detail. In both cases the concept of ductility is explained in detail. Results of response spectrum analyses of tall buildings asymmetric in plan constructed in Bengaluru using ETABS are mentioned.Application of capacity spectrum is explained and illustrated using ETABS for a tall building. Research output of retrofitting techniques is mentioned. Response spectrum analysis using PYTHON is illustrated with the hope that itcould be aless expensive approach as it isan open source code. A new approach of creating a fictitious (imaginary)boundary to obtain blast loads on below-ground structures devised by the author is presented with an example. Aimed at senior undergraduates and graduates in civil engineering, earthquake engineering and structural engineering, this book: Explains in a simple manner the fundamentals of structural dynamics pertaining to earthquake and blast resistant designIllustrates seismic resistant designs such as ductile design philosophy and limit state design with the use of capacity spectrumDiscusses frequency domain analysis and Laplace transform approach in detailExplains solutions of building frames using software like ETABS and STAADCovers numerical simulation using a well-known open source tool PYTHON
OCLC-licensed vendor bibliographic record.
Keywords: Earthquake resistant design; TECHNOLOGY / Engineering / Civil